A UHPLC–MS/MS method for the quantification of Δ9-tetrahydrocannabinol and cannabidiol in decoctions and in plasma samples for therapeutic monitoring of medical cannabis. (6th November 2018) - Barco, Sebastiano; Fucile, Carmen; Manfredini, Luca; Grandis, Elisa De; Gherzi, Marcella; Martelli, Antonietta; Tripodi, Gino; Mattioli, Francesca; Cangemi, Giuliana
Aim: Monitoring of blood levels of Δ9-tetrahydrocannabinol (THC) and cannabidiol (CBD) is necessary for optimization of administration of medical cannabis. We describe the validation of a ultra-HPLC–MS/MS method for quantifying THC and CBD from plasma and decoctions and its application for therapeutic drug monitoring.Materials & methods: Analyses were performed by using a TSQ Quantiva™ Triple Quadrupole coupled to a Ultimate 3000 UHPLC system with atmospheric pressure chemical ionization after sample preparation with a straightforward method with deuterated internal standards.Results:  The method has been validated following EMA guidelines and is linear in plasma from 0.16 to 10 ng/ml for both THC and CBD and in decoctions from 4.7 to 600 ng/ml.Conclusion: Given the unpredictable pharmacokinetic behavior of THC and CBD in patients, monitoring of plasma concentrations is strongly recommended for patients under treatment with medical cannabis.